Comparative Genomic Analysis of Xanthomonas campestris pv. campestris Isolates BJSJQ20200612 and GSXT20191014 Provides Novel Insights Into Their Genetic Variability and Virulence - Chen, Denghui; Zhong, Xionghui; Cui, Jian; Li, Hailong; Han, Rui; Yue, Xiangqing; Xie, Jianming; Kang, Jungen (Frontiers in Microbiology, 2022)
Black rot is a disease that has a severe impact on cabbage yield and quality in China. Xanthomonas campestris pv. campestris (Xcc) is the causal agent of black rot of Brassicaceae crops. So far, the whole genomic sequences of more than 30 Xcc isolates have been sequenced; however, little information about genomic variability and virulence has been reported. In this study, 12 Xcc isolates were isolated from diseased cabbage leaves in seven Chinese provinces and two municipalities from July 2019 to November 2020. Pathogenicity analysis showed that isolate GSXT20191014 was more aggressive than BJSJQ20200612 and HRIW 3811 on cabbage inbred line 1371. Both BJSJQ20200612 and GSXT20191014 were sequenced and comparatively analyzed. The results showed that BJSJQ20200612 and GSXT20191014 have a single circular chromosome comprising 5,115,975 and 4,975,682 bp, respectively. Compared to the other six sequenced strains, 26 and 47 variable genomic regions were found in BJSJQ2020061 and GSXT20191014 genomic sequences, respectively. The variable genomic regions could be responsible for the genetic variation in Xcc strains and have led to the differences in type III secreted effector repertoires, virulence factors and secreted proteins between these two strains. Among the identified secreted proteins, two copies of peptidase S8/S53 were found in GSXT20191014-specific chromosomal segments. The common effectors xopR, xopH, avrBs1, and xopAH are found in most Xcc genomes, but they are absent in the GSXT20191014 genome. Variations in the composition of exopolysaccharides (EPS) and lipopolysaccharides (LPS) may aid GSXT20191014 isolate infections to evade recognition by the host immune system. Our results revealed a direct correlation between genomic variability and Xcc virulence. We also developed several markers for detecting BJSJQ20200612 and GSXT20191014 isolates and further tested the rest of our other 10 isolates. Finally, the isolated Xcc strains were classified into three genetic subgroups by specific molecular markers and multilocus sequence typing (MLST) approach. BJSJQ20200612 and GSXT20191014 isolates were also classified into two subgroups of Xcc according to the core-genome-based phylogenetic tree. This study extended our understanding of Xcc genomic features and provided the foundation to further characterize the mechanisms for Xcc virulence and a clue for black rot resistance breeding.